A randomized trial to assess the impact of early steroid withdrawal on growth in pediatric renal transplantation: the TWIST study - Grenda, Ryszard; Watson, A.; Trompeter, R.; Tönshoff, Burkhard; Jaray, J.; Fitzpatrick, M.; Murer, L.; Vondrak, K.; Maxwell, H.; Van Damme-Lombaerts, R.; Loirat, C.; Mor, E.; et al. (American journal of transplantation, 2010)
Minimizing steroid exposure in pediatric renal transplant recipients can improve linear growth and reduce metabolic disorders. This randomized multicenter study investigated the impact of early steroid withdrawal on mean change in height standard deviation score (SDS) and the safety and efficacy of two immunosuppressive regimens during the first 6 months after transplantation. Children received tacrolimus, MMF, two doses of daclizumab and steroids until day 4 (TAC/MMF/DAC, n = 98) or tacrolimus, MMF and standard-dose steroids (TAC/MMF/STR, n = 98). Mean change in height SDS was 0.16 ± 0.32 with TAC/MMF/DAC and 0.03 ± 0.32 with TAC/MMF/STR. The mean treatment group difference was 0.13 (p < 0.005 [95% CI 0.04-0.22]), 0.21 in prepubertal (p = 0.009 [95% CI 0.05-0.36]) and 0.05 in pubertal children (p = ns). Frequency of biopsy-proven acute rejection was 10.2%, TAC/MMF/DAC, and 7.1%, TAC/MMF/STR. Patient and graft survival and renal function were similar. Significantly greater reductions in total cholesterol and triglycerides but significantly higher incidences of infection and anemia were found with TAC/MMF/DAC (p < 0.05 all comparisons). Early steroid withdrawal significantly aided growth at 6 months more so in prepubertal than pubertal children. This was accompanied by significantly better lipid and glucose metabolism profiles without increases in graft rejection or loss.